(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
Surgical interventions play a pivotal role in modern medicine, addressing a wide array of medical conditions ranging from routine procedures to complex, life-saving surgeries. This article aims to provide a comprehensive overview of various types of surgical interventions, emphasizing their methodologies, outcomes, and the current state of research in the field. Through an extensive literature analysis, we explore the evolution of surgical techniques, their impact on patient outcomes, and discuss future directions for advancements in surgical interventions.